Autogenous shrinkage prediction models and microstructure of UHPC with single or binary addition of an expansive agent and steel fibers - Weng, JiaRui; Liao, WenCheng (Frontiers in Materials, 2024)
The low water/binder ratio of ultra-high performance concrete (UHPC) often results in its high autogenous shrinkage. Our study explored the effect of the single or binary addition of CaObased expansive agent (CEA), steel fibers on flowability, compressive strength, flexural strength, microstructure and autogenous shrinkage of UHPC. X-ray diffraction (XRD), thermogravimetric (TG) analysis, scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) were applied to reveal the effects of CEA and steel fibers on hydration products and microstructure characteristics of UHPC. Experimental results display the autogenous shrinkage of UHPC decreased markedly with single or binary addition of CEA, steel fibers. Relative to the control group, autogenous shrinkage of UHPC with 2.5% dosage of single steel fibers, 6% dosage of single CEA, binary addition of 2.5% steel fibers and 6% CEA decreased 17.8%, 10.9%, and 30.8% at 180d, respectively. Steel fibers could enhance the mechanical performance of UHPC, nevertheless, they would decrease the flowability of UHPC. Meanwhile, the addition of CEA in the UHPC mixture not only maintained mechanical properties and flowability but also decreased the autogenous shrinkage. Diffraction peak intensity and endothermic peak of Ca(OH)2, pore volume of 10-50 nm diminished with the content of CEA, however, that of C-S-H gel and ettringite increased. The prediction accuracy of 9 shrinkage models (FHWA model, Lee model, Yoo model, JSCE model, B4 model, JonassonH model, Eurocode 2 model, CEB model, DilgerW model) are analyzed with RE, 2 new R and autogenous shrinkage of UHPC in this paper.